Amination of black liquor and the application in the ready-mixed wet mortar - Zheng, Dafeng (Environmental technology, 2018)
In order to extend the application of black liquor (BL), amino group was introduced in lignin through Mannich reaction. The structure of the aminated black liquor (ABL) was characterized with FT-IR, elemental analysis, the zeta potential and the inherent viscosity. The foam generated by ABL was more stable, for the surface tension was lower. The results of the mortar test indicated that the water-retention rate of the fresh mortar incorporated with 0.3 wt% ABL was 89.1%; the consistency loss was about 39.7% after 4 h. When the dosage was less than 0.3 wt%, ABL could increase the bond strength of the hardened mortars. The results showed that ABL could be used as an effective ready-mixed wet mortar admixture. This study not only provided a new method to develop new mortar admixture, but also alleviated the pollution of BL